HEPATOPATHOPHYSIOLOGY AND DIETARY TYPES IN LIVER DISEASES (Web of Teachers: Inderscience Research, 2025)
Liver diseases encompass a wide range of pathophysiological conditions that severely affect liver function. The liver plays a critical role in metabolism, detoxification, and storage of nutrients. Pathological changes in liver function can result in conditions like cirrhosis, non-alcoholic fatty liver disease (NAFLD), hepatitis, and liver fibrosis. Proper management of these diseases often includes dietary interventions, which can be tailored to mitigate disease progression and improve the patient’s quality of life. This paper explores the underlying mechanisms of hepatopathophysiology and the types of diets recommended for various liver conditions.